2016
DOI: 10.1111/jam.13276
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofLactobacillus plantarumCCFM0236 on hyperglycaemia and insulin resistance in high-fat and streptozotocin-induced type 2 diabetic mice

Abstract: The method of α-glucosidase inhibitory activity could be effectively used to screen potential hypoglycaemic products and Lact. plantarum CCFM0236 might be a promising therapeutic agent for ameliorating type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(52 citation statements)
references
References 32 publications
6
42
0
4
Order By: Relevance
“…Therefore, in the present study, living strain was selected to feed mice. Results showed that L. acidophilus KLDS1.0901 treatment could significantly decrease food intake and FBG level and increase BW ( Figure 3A), which is consistent with other studies (Li et al, 2016). HbA1c, which is a clinical diagnostic parameter for diabetes, reflects the average plasma glucose concentration over a period of time.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, in the present study, living strain was selected to feed mice. Results showed that L. acidophilus KLDS1.0901 treatment could significantly decrease food intake and FBG level and increase BW ( Figure 3A), which is consistent with other studies (Li et al, 2016). HbA1c, which is a clinical diagnostic parameter for diabetes, reflects the average plasma glucose concentration over a period of time.…”
Section: Discussionsupporting
confidence: 89%
“… 29 - 33 Moreover, several strains of L. plantarum species have been reported to improve the glycemic control in obese and diabetic patients, likely via their carbohydrate-utilizing genes. 34 , 35 Studies also indicate that administration of Bifidobacterium animalis, B. breve , and B. longum led to amelioration of glucose intolerance. 28 , 36 - 38 While results of individual studies have been quite variable, a recent meta-analysis has shown that these probiotics improve glycemic control and significantly decrease the risk of gestational diabetes mellitus in pregnant women.…”
Section: Probiotics In Diabetesmentioning
confidence: 99%
“…Accumulating evidence indicates that supplementation with specific probiotics in dietary interventions could affect the host metabolism and modulate the glucose homeostasis in an animal model and human studies (Holmes et al, 2012;Cano et al, 2013;Yadav et al, 2013;Cheng et al, 2015;Aoki et al, 2017). Some species within the Lactobacillus demonstrated anti-obesity (Karimi et al, 2015;Li et al, 2016) or anti-diabetic (Honda et al, 2012;Li et al, 2016) effects in animal models or humans.…”
Section: Introductionmentioning
confidence: 99%